Liquidity from two lending facilities - Anbil, Sriya; Vossmeyer, Angela (Journal of Financial Intermediation, 2021)
We examine how the threat of disclosure (stigma) changes the quality of banks that approach emergency lending facilities. We study a financial crisis where two confidential facilities were available to banks. Unexpectedly, a partial list of bank names from one facility was published, suddenly stigmatizing that facility. We find that the composition of banks that approached each facility changed, where the newly stigmatized facility attracted weaker banks that maintained smaller liquidity buffers, while the alternative confidential facility attracted both weaker and stronger banks. Our results shed light on how stigma prevents regulators from reaching many banks to inject critical liquidity into the banking sector during a crisis.